Parameters of variability in the execution of the serve by skilled volleyball players - N.V. , Lutkova; Makarov, Yu.M.; Egorenko, L.A.; Dakshevich, N.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the parameters of variability in the execution of serves by skilled volleyball players. Methods and structure of the study. The following parameters were assessed during the study: dynamometric data, the accuracy of muscle force differentiation and the magnitude of their deviation from the calculated value, agility coefficients in running and jumping, the ability to distinguish time intervals, as well as the endurance of the nervous system and its ability to switch to movements performed at different speeds. Serving effectiveness was assessed based on the type of serve (precision serve, power serve, “hybrid” serve). Ten matches of leading teams were analyzed using the professional software Data Volley 4Pro. The study subjects were 12 male athletes holding the qualifications of Candidate Master of Sports and Master of Sports, participants in the Russian Volleyball Championship. Results and conclusions. 1. It was established that for precision serves, the key parameters are the differentiation of muscular effort (25% and 50% of maximum) and the difference in time intervals (10 and 30 seconds). 2. It was determined that for power serves, the determining indicators are the jump agility coefficient, the level of nervous system endurance, and its ability to switch to movements at different speeds. 3. It was found that for hybrid serving, the determining factors are parameters of jumping agility, maximum hand strength, accurate discrimination of time intervals (10, 30, and 60 seconds), differentiation of muscular effort (75% of maximum), high levels of endurance, and the nervous system’s ability to switch between movements at different speeds.